2012
DOI: 10.1177/1477153512450452
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an online protocol for assessing the luminous environment

Abstract: We developed a web application to investigate online-based experiments for the psychovisual assessment of luminous environments. We reproduced online a laboratory experiment conducted in a virtual environment, in which the luminous environment of an office room lit by different combinations of ambient/task lighting was assessed by observers. A control panel of 30 observers performed both experiments. Statistical analyses revealed no statistically significant differences between data collected in the laboratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 26 publications
1
23
0
1
Order By: Relevance
“…Then, mean values and 95% confidence intervals (95% CI) were computed and are presented in Figure 2 (left bars LabExp-CtrlPnl, middle bars OnlineExpCtrlPnl). According to findings presented in previous work, 21 LabExp-CtrlPnl conducted with the simulator in a virtual environment, are consistent with previous work (including those carried out in realworld) aiming at identifying the most suitable hybrid ambient/task lighting installations in offices. In addition, no statistical difference between LabExpCtrlPnl and OnlineExp-CtrlPnl was found.…”
Section: Main Results Of Labexp-ctrlpnl and Onlineexp-ctrlpnlsupporting
confidence: 90%
See 1 more Smart Citation
“…Then, mean values and 95% confidence intervals (95% CI) were computed and are presented in Figure 2 (left bars LabExp-CtrlPnl, middle bars OnlineExpCtrlPnl). According to findings presented in previous work, 21 LabExp-CtrlPnl conducted with the simulator in a virtual environment, are consistent with previous work (including those carried out in realworld) aiming at identifying the most suitable hybrid ambient/task lighting installations in offices. In addition, no statistical difference between LabExpCtrlPnl and OnlineExp-CtrlPnl was found.…”
Section: Main Results Of Labexp-ctrlpnl and Onlineexp-ctrlpnlsupporting
confidence: 90%
“…Their main results are then highlighted. These experiments are already presented in details in previous work 21 and are summarised in this section for the sake of clarity. Table 2 presents the photometric characteristics of the 26 evaluated stimuli.…”
Section: Psychovisual Experiments With CDmentioning
confidence: 98%
“…Mahdavi and Eissa [2002] concluded that the results of the evaluation of non-daylit office spaces in REs were similar to the results obtained by using highquality computer renderings. Villa and Labayrade [2013] compared the results obtained by an online laboratory experiment to evaluate virtual luminous environments to those obtained in a real laboratory experiment. Their findings revealed no differences between the data collected in the laboratory and online.…”
Section: Introductionmentioning
confidence: 97%
“…The difficulty of conducting full-scale experimental studies has been stated by numerous researchers [Newsham et al 2005;Villa and Labayrade 2013]. To conduct rigorous scientific architectural or lighting research in Real Environments (REs) brings a series of challenges even for the most experienced 21:2 • C. Moscoso et al researcher.…”
Section: Introductionmentioning
confidence: 99%
“…on the assessment of digital images for lighting quality research. Their study found that significant effects could be identified with 40 subjects despite systematic error due to uncontrolled conditions and the variance in p-value was constant with ≥100 subjects (0.0002) 35 . Where controlled experiments are time-consuming, an online protocol allows for more widely distributed experiments.…”
Section: Existing Experimental Studiesmentioning
confidence: 99%